Implementation of Mutual Legal Assistance in Law Enforcement of the Crime of Piracy by the Indonesian Navy (Study. MT. Orkim Harmony) - Handy Kurniawan; Agung Pramono; Mangisi Simanjuntak (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
The crime of piracy is transnational; handling it requires bilateral or multilateral cooperation; according to Article 9 (2) of the Republic of Indonesia Law, Number 1 of 2006, only the National Police Chief and the Attorney General can request Mutual Legal Assistance. Still, the Indonesian Navy has applied for Mutual Legal Assistance against the MT Orkim Harmony piracy case. With these facts, this paper tries to see how the efforts of the Central Authority (Polri and Prosecutors) in assisting law enforcement by the Navy and how the implementation of the Mutual Legal Assistance agreement. The research method uses normative law or library research with a statute approach and analyzes the data in this study using qualitative normative analysis. From the results of the study